The Influence of Facebook Advertising on Increasing Sales of Micro, Small, and Medium Enterprise Products in Bandung - A Rezma; R Elsa; A Zahrotun (Universitas Komputer Indonesia, 2022)
Increasing social media involvement in MSME business sales is now growing, starting with the number of sales made through social media networks or the internet. Behind the development of sales from social media, there is a platform that provides offers to advertise or promote products on the platform. Facebook Advertising (Facebook Ads) evolved to help sellers or online business sellers promote sales. The purpose of this study was to determine how the influence of Facebook advertising on the increase in sales of Micro, Small and Medium Enterprises (MSME) in the city of Bandung. In this study, we use quantitative research methods with descriptive studies to several respondents, especially those in the city of Bandung in order to strengthen the data that will be needed. The results of this study indicate that using Facebook Ads to increase sales of a product is sufficient to influence product sales, then it is comparable to the aims and objectives of the study. However, with the increasing number of competitors using Facebook Ads as a promotional medium, of course, some improvements are needed in the manufacture of advertising products so that the audience can be interested when they see the products to be marketed. Of course, in this case it proves that the influence of Facebook Ads as a promotional medium can affect sales increases so that it can make it easier for other businessmen to promote their products.